Blockade of Uttroside B-Induced Autophagic Pro-Survival Signals Augments Its Chemotherapeutic Efficacy Against Hepatocellular Carcinoma - Nath, Lekshmi R.; Swetha, Mundanattu; Vijayakurup, Vinod; Thangarasu, Arun Kumar; Haritha, Nair Hariprasad; Shabna, Anwar; Aiswarya, Sreekumar U.; Rayginia, Tennyson P.; Keerthana, C. K.; Kalimuthu, Kalishwaralal; Sundaram, Sankar; Lankalapalli, Ravi Shankar; et al. (Frontiers in Oncology, 2022)
Our previous study has demonstrated that Uttroside B (Utt-B), a saponin isolated from the leaves of Solanum nigrum Linn induces apoptosis in hepatic cancer cells and exhibits a remarkable growth inhibition of Hepatocellular Carcinoma (HCC). Our innovation has been granted a patent from the US (US 2019/0160088A1), Canada (3,026,426.), Japan (JP2019520425) and South Korea (KR1020190008323) and the technology have been transferred commercially to Q Biomed, a leading US-based Biotech company. Recently, the compound received approval as ‘Orphan Drug’ against HCC from US FDA, which reveals the clinical relevance of evaluating its antitumor efficacy against HCC. In the present study, we report that Utt-B promotes pro-survival autophagy in hepatic cancer cells as evidenced by the increased expression of autophagy-related proteins, including LC3-II, Beclin1, ATG 5, and ATG 7, as well as a rise in the autophagic flux. Hence, we investigated whether Utt-B-induced autophagic response is complementing or contradicting its apoptotic program in HCC. Inhibition of autophagy using the pharmacological inhibitors, Bafilomycin A1(Baf A1), and 3-methyl adenine (3-MA), and the biological inhibitor, Beclin1 siRNA, significantly enhances the apoptosis of hepatic cancer cells and hence the cytotoxicity induced by Utt-B. We also found increased expression of autophagy markers in Utt-B-treated xenografts derived from HCC. We further analyzed whether the antimalarial drug, Chloroquine (Cqn), a well-known autophagy inhibitor, can enhance the anticancer effect of Utt-B against HCC. We found that inhibition of autophagy using Cqn significantly enhances the antitumor efficacy of Utt-B in vitro and in vivo, in NOD SCID mice bearing HCC xenografts. Taken together, our results suggest that the antitumor effect of Utt-B against HCC can be further enhanced by blocking autophagy. Furthermore, Utt-B in combination with Cqn, a clinically approved drug, if repurposed and used in a combinatorial regimen with Utt-B, can further improve the therapeutic efficacy of Utt-B against HCC.